Movement of Negroes , Its Causes , Its Aims And Ways of Elimination it: ( 255 – 270 A.H. ) ( 869 - 883 A.D. ) - YOUNIS, SAWSAN BAHJAT (Al-Adab Journal, 2019)
Revolution of negroes was dangerous movement . It threatened entity of Abbaside state in the core and made it engaged in for fourteen years . It is not enough to understand comprehension of man’s ambition who stirred it or made situation of caliphate disordered merely . But no doubt to analyze condition of who joined his leadership , motives beyond made them to those actions to fight enthusiastically with astonish a long duration of revolution. Although allegation of owner of negroes that divine caring has sent him to rescue oppressed slaves . It had instructed , directed him , helped him though he disguised with prophecy , message , also he alleged his descent to ALALAWI to be acquired as an honor , but he did not declare principles of Shii doctrine , but he promised with declarations of Al – Khawarej who denied heritage which based on Abbaside and Alwayeen altogetherUndoubtedly that political ambitions of Ali Bin Mohammed are represented by seizure over power which it is considered as real urge for the movement . Where it restricted its rush largely , it limited it within a group of negroes and made other away gradually of groups which contributed in themAnd so on the movement of negroes finished after left behind it awful effects of destruction and sabotage . The most important thing of them is the class spirit which was described in economic war through it , significance of civil engineering in its buildings , discover of weakness of caliphate and its potential power at one time . The movement of negroes was not of strength at the beginning to be able to defeat army of caliph , but the caliph did not assess movement of negroes as its capacity . He neglected it more , where he sent non qualified Turkish leaders to pass through like these battles , but even authorization , power in Baghdad have made them affect to prefer to remain at the city to follow up matters over there , to take what he prefers of moneys of caliphate without any right . The Arab element in the battle is the strongest , the more demanded to take its position within like these locations of fighting as we found out at Al – Mowaffaq , his son Abu Al – Abbas of plucky , strictness and fighting experience